BERADAB DENGAN TENAGA BOLEH BAHARU - Muhammad Nazry Chik; Liyana Yahya; Afifi Zainal (PERINTIS eJournal, 2021)
Renewable Energy has been identified as one of the energy resource contributors in the national electricity supply industry, known for its sustainability, environmental friendly and its impactful role in supporting the country’s commitment in reducing the carbon dioxide gas (CO2). Several policies, program, act and incentives have been devised and launched by the government in promoting the development and use of renewable energy, with a visible positive progress ever since. However, to complement this achievement, it is equally crucial that an underlying principle and spiritual meaning of renewable energy and the end-of-mind of its development be made known and understood. Thus, ‘adab’ (loosely equivalent to ‘ethic’ or ’manner’) in renewable energy is elucidated in this article, making sense of the word ‘adab’ first, before delving into intricacies of relevant knowledge (‘ilm) in the renewable energy industry. In completing the meaning of adab to renewable energy, four frameworks are proposed to be adhered: (i) developing renewable energy via good engineering conducts and practices, (ii) to grow renewable energy by taking into account its various benefits other than electricity alone, (iii) to pursue it in a sustainable manner, and (iv) to take into account how renewable energy can benefit a society at large.